2018
DOI: 10.1139/cjpp-2017-0113
|View full text |Cite
|
Sign up to set email alerts
|

TNF-α antagonism with etanercept enhances penile NOS expression, cavernosal reactivity, and testosterone levels in aged rats

Abstract: Erectile dysfunction (ED) has been reported to be associated with inflammation. This study investigated the effects of tumor necrosis factor alpha (TNF-α) inhibitor etanercept on penile neuronal nitric oxide synthase (nNOS) and endothelial nitric oxide synthase (eNOS) expressions, testosterone concentrations, neurogenic and endothelium-dependent relaxations of corpus cavernosum (CC), and circulating and cavernosal levels of inflammatory markers in aged rats. Animals were separated into control, aged, and etane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Briefly, in an animal model of hypogonadism, where there are reduced testosterone levels, inflammatory cytokines such as IL-6, IL-1β, and TNF-α were said to be elevated and only IL-6 was reduced after testosterone treatment [ 81 , 82 ]. Similarly, findings from human studies have also shown that there are increased inflammatory cytokines in hypogonadism [ 83 , 84 ].…”
Section: Mechanisms Through Which Statins May Impact Male Reproductionmentioning
confidence: 99%
“…Briefly, in an animal model of hypogonadism, where there are reduced testosterone levels, inflammatory cytokines such as IL-6, IL-1β, and TNF-α were said to be elevated and only IL-6 was reduced after testosterone treatment [ 81 , 82 ]. Similarly, findings from human studies have also shown that there are increased inflammatory cytokines in hypogonadism [ 83 , 84 ].…”
Section: Mechanisms Through Which Statins May Impact Male Reproductionmentioning
confidence: 99%
“…found sex hormones in mice regulates visceral adipose tissue inflammation via shaping the transcriptional landscape of Treg cells in a BLIMP1 transcription factor-dependent manner (25). Aged rats treated with etanercept (a TNF-a inhibitor) showed obviously higher inflammatory markers while decreased serum testosterone (26). In induced colitis mouse model, E2 could inhibit inflammatory cytokines to produce an antiinflammatory effect through the estrogen receptor b signaling pathway (27).…”
Section: Introductionmentioning
confidence: 99%
“…Human recombinant interleukin-37 (IL-37), an anti-inflammatory cytokine of the interleukin-1 family, has been reported to favor vascular endothelial function in old age by increasing NO bioavailability and the phosphorylation of AMP-activated kinase (AMPK), as well as reducing levels of ROS [ 220 ]. Etanercept (TNF-α antagonism) treatment has been demonstrated to be useful to improve aging-impaired endothelium-dependent relaxant responses in rats [ 221 ]. Akt activation stimulates eNOS phosphorylation, increases NO production, and reduces oxidative stress [ 222 ].…”
Section: New Therapeutic Approaches Targeted Endothelial Dysfunctimentioning
confidence: 99%